The occurrence of piroplasms in various South African black rhinoceros (Diceros bicornis) populations - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.